Directed evolution of a model primordial enzyme provides insights into the development of the genetic code. - Manuel M Müller; Jane R Allison; Narupat Hongdilokkul; Laurent Gaillon; Peter Kast; Wilfred F van Gunsteren; Philippe Marlière; Donald Hilvert (PLoS Genetics)
The contemporary proteinogenic repertoire contains 20 amino acids with diverse functional groups and side chain geometries. Primordial proteins, in contrast, were presumably constructed from a subset of these building blocks. Subsequent expansion of the proteinogenic alphabet would have enhanced their capabilities, fostering the metabolic prowess and organismal fitness of early living systems. While the addition of amino acids bearing innovative functional groups directly enhances the chemical repertoire of proteomes, the inclusion of chemically redundant monomers is difficult to rationalize. Here, we studied how a simplified chorismate mutase evolves upon expanding its amino acid alphabet from nine to potentially 20 letters. Continuous evolution provided an enhanced enzyme variant that has only two point mutations, both of which extend the alphabet and jointly improve protein stability by >4 kcal/mol and catalytic activity tenfold. The same, seemingly innocuous substitutions (Ile→Thr, Leu→Val) occurred in several independent evolutionary trajectories. The increase in fitness they confer indicates that building blocks with very similar side chain structures are highly beneficial for fine-tuning protein structure and function.